Development of a Software to Determine Disturbances in the Acid-Base Balance in Human Blood. - Reyes-Lazalde, A.; Reyes-Monreal, M.; Pérez-Bonilla, M. E.; Reyes-Luna, R. (Revista Mexicana de Ingeniería Biomédica, 2026)
In intensive care units, one of the most frequent emergencies occurring in patients in critical condition is acid-base imbalance. The ability to proficiently manage such patients is achieved through many years of hospital practice. The correct quantification of such imbalances allows for the detection of complex alterations. Although this area is fundamental for the clinical management of many patients, nonspecialist doctors rarely receive the appropriate training. In addition, the learning required to master this area is difficult for doctors due to the level of mathematics involved. There are two online support programs available on the internet for determining blood pH based on the Stewart Model, along with a spreadsheet for the patient's collected data. Generally, the calculation of hydrogen ion concentration [H] uses a table of equivalences between pH y [H] for discontinuous values of pH, with the Davenport diagram used manually. However, none of these programs unite the methods of classic calculus, chemistry and physicochemistry. This study develops software for the teaching and calculation of acid-base imbalance that combines all the relevant methods, such as the Henderson-Hasselbalch equation, the Siggard- Anderson modified excess base equation, the anion gap calculation, the computational implementation of the Davenport diagram, the calculus of [H] for any value of pH, the calculus for the compensatory process, and the Stewart Model. The combined use of these methods is complementary, synergic and permits a preliminary diagnosis that interprets and understands both respiratory alterations and miniscule metabolic or mixed alterations. With this software, a doctor can identify acid-base imbalances and the occurrence of compensatory processes, such as the concentration of acid or base, in order to restore pH, while many simulations of clinical cases can be carried out in the classroom for medical training purposes.